Dinamika Persepsi Nasabah Pembiayaan UMKM di BMT NU Kantor Wilayah Ngoro terhadap Keberlanjutan Usaha - Elsa Setya Putri; Naily El Muna; Ashlihah Ashlihah (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economy, yet limited access to capital remains a major obstacle. Sharia financing from Islamic microfinance institutions is expected to support MSME business sustainability. This study aims to analyze MSME customers' perceptions of sharia financing, identify the internal and external factors influencing these perceptions, and examine the dynamics of perception changes after receiving multiple financing facilities. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observation, and documentation from MSME customers receiving sharia financing at BMT NU Ngoro Regional Office. Data validity was ensured through source and method triangulation. The findings indicate that MSME customers generally hold a positive perception of sharia financing. It is perceived as offering easy procedures, good service quality, and compliance with Islamic principles, thereby supporting capital increase and business sustainability. Perceptions are influenced by internal factors such as business experience and motivation, as well as external factors including market conditions and competition. Furthermore, customers' perceptions tend to become progressively more positive as their experience with receiving financing increases. The significant role of interpersonal service quality and mentoring in shaping positive perceptions is a key finding. In conclusion, sharia financing at BMT NU Ngoro Regional Office plays a vital role in supporting MSME business sustainability. Consequently, continuous improvement in service quality and business assistance is necessary.